The amendment proposals for articles 9, 24, 32 of the Constitution, recently approved by the Senate: II. The environment and health impairment - Bompiani, Adriano (Medicina e Morale, 1992)
In this second part (the first part was published in issue 2/92 pages 233-255) the author deals with the question of the "healthiness" of living and working environments from a legal point of view. In particular he concentrates on the concepts of "health impairment" and "biological damage". Considerable space is given to the problem of compensation for damages with reference to health impairment. The recent process of extension of health impairment from civil responsibility to social security is also mentioned.